2021
DOI: 10.1002/jia2.25751
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and frailty among women with and without HIV in the United States: a cross‐sectional analysis

Abstract: Introduction Frailty is frequently observed among people with HIV, and food insecurity is associated with frailty in the general population. Evidence is scarce on the associations between food insecurity and frailty among women with HIV who may be particularly vulnerable to the impacts of food insecurity. The goal of this study was to assess associations between food insecurity and frailty among women with and without HIV. Methods There were 1265 participants from the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…To understand the independent association of food insecurity with non-adherence, we used longitudinal multinomial logistic regression with the 4-category adherence variable as the outcome and food insecurity as the explanatory variable, controlling for covariates and using complete case analysis. The resulting adjusted relative-risk ratios (RRRs) [52][53][54], as described in our previous published work [55], are interpreted as the association of food insecurity with each non-adherence category (< 75%, 75-94%, and 95-99% adherence) versus 100% adherence. All regressions included random effects to allow for unexplained individual-level variation.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the independent association of food insecurity with non-adherence, we used longitudinal multinomial logistic regression with the 4-category adherence variable as the outcome and food insecurity as the explanatory variable, controlling for covariates and using complete case analysis. The resulting adjusted relative-risk ratios (RRRs) [52][53][54], as described in our previous published work [55], are interpreted as the association of food insecurity with each non-adherence category (< 75%, 75-94%, and 95-99% adherence) versus 100% adherence. All regressions included random effects to allow for unexplained individual-level variation.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of frailty amongst people living with HIV remains unclear though a recent systematic review of people over 50 years living with HIV (26 studies, 6584 cases) using the FFP reported a pooled prevalence of 10.9% for frailty and 47.2% for prefrailty comparable with 11% and 42% of community-dwelling older adults without HIV, though heterogeneity between studies was high making comparison challenging [19 ▪ ]. Further studies have been conducted since using various frailty diagnostic tools with the results summarized below (Table 1) [20–24,25 ▪▪ ,26,27 ▪ ,28–30,31 ▪▪ ].…”
Section: Prevalencementioning
confidence: 99%
“…Although we only detected an association with overall frailty and weak grip strength in our sample, data in the general population indicate that undernutrition can adversely affect each criterion used in the FFP (e.g., weight loss, exhaustion, physical activity, slow gait speed and grip strength; Bonnefoy et al, 2015). In the limited data among PWH, very low food security (i.e., high food insecurity) was associated with prefrailty and frailty among women regardless of HIV status (Tan et al, 2021). Very low food security is defined as various indications of disrupted eating patterns and decreased food consumption (Tan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the limited data among PWH, very low food security (i.e., high food insecurity) was associated with prefrailty and frailty among women regardless of HIV status (Tan et al, 2021). Very low food security is defined as various indications of disrupted eating patterns and decreased food consumption (Tan et al, 2021). Ensuring access to healthy food options may be an important component of prevention or reversing numerous components of physical function and frailty, beyond simply weight loss (Willig et al, 2016).…”
Section: Discussionmentioning
confidence: 99%